PENGEMBANGAN MEDIA SMART APRON UNTUK PEMBELAJARAN MENGENAL BENTUK GEOMETRI PADA ANAK KELOMPOK A - Allan Firman Jaya; Maria Ulfa (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2021)
This research aims to develop a media in the form of an apron (apron) to teach children's knowledge about children's geometric abilities. Child geometry is included in the cognitive development of early childhood. In an effort to develop the media, the Sugiyono model is used which consists of 1) potential and problems, 2) data collection, 3) product design, 4) design validation by material experts and media experts and product revisions. Product trials were not carried out in this research due to the pandemic.